Performance of Non-Uniform Constellations for 5G 60 GHz Wireless LANs - Hasdemir, Alper Ozan; Tureli, Ufuk (IEEE, 2016)
To achieve higher transmission rates and make use of unlicensed frequency bands around 60 GHz millimeter-wave, novel non-uniform 64 QAM constellation created for IEEE 802.11ay task group were simulated for OFDM modulation under 60GHz indoor channels. The IEEE 802.11ad task group cubicle, conference and living room indoor 60 GHz channels were used to show bit error rate (BER) improvement.
Keywords: 60 GHz; indoor channel; 64QAM; 5G technology; modulation; OFDM; Engineering